Financial LLM For Stock Price Analysis And Investment Recommendation - Kuruvilla, Jeevan Sunil; M, Mythily (Journal of Telematics and Informatics, 2025)
The integration of Large Language Models (LLMs) into financial analysis represents a transformative shift in how financial data is interpreted and utilized for market predictions and investment decisions. Traditionally, financial analysis has relied on structured quantitative data, such as stock prices, economic indicators, and company fundamentals. However, the sheer volume of unstructured textual data available from sources like financial news, analyst reports, and social media has made it increasingly important to integrate natural language processing (NLP) capabilities. This research explores the design and implementation of a novel Financial LLM framework that bridges the gap between traditional financial theories and advanced deep learning techniques, offering a more comprehensive and accurate approach to financial forecasting and decision-making. The framework developed in this study employs time series forecasting models, such as Long Short-Term Memory networks (LSTMs) and Temporal Fusion Transformers (TFTs), which are particularly adept at modeling temporal dependencies and predicting stock price movements. These models analyze historical stock prices and market trends to forecast short-term price fluctuations and volatility. The use of LSTMs, known for their ability to capture long-term dependencies in sequential data, and TFTs, which incorporate attention mechanisms to focus on the most relevant time periods, ensures that the model can handle the complexity and volatility of the financial market. In addition to the price prediction models, the framework also incorporates sentiment analysis, which plays a crucial role in understanding market dynamics. By using fine-tuned LLMs, such as FinBERT and BloombergGPT, the system processes unstructured textual data from a wide array of sources, including news articles, analyst reports, and even social media platforms. These sentiment models are trained to understand financial terminology and detect market sentiment, which can often be a critical driver of stock price movements. The sentiment scores generated by these models provide an additional layer of insight into market conditions, helping to predict future market behaviors that might not be immediately evident from the numerical data alone. Furthermore, the framework incorporates a variety of alternative datasets to enhance the predictive accuracy and depth of the analysis. These datasets include macroeconomic indicators, company fundamentals, search trends, and even satellite imagery. By including such diverse and unconventional data sources, the framework is better equipped to capture a broader range of market signals, such as consumer behavior trends, geopolitical events, or supply chain disruptions, which can significantly impact stock prices and market sentiment. The system also integrates sophisticated portfolio optimization techniques to recommend investment strategies. Reinforcement Learning (RL) is employed to optimize asset allocation, ensuring that the portfolio is balanced in a way that maximizes returns while minimizing risk. Modern Portfolio Theory (MPT) further helps in determining the ideal mix of assets to achieve the highest possible return for a given level of risk. These portfolio optimization models are crucial in helping investors manage risk and maximize their long-term returns, particularly in volatile market conditions. Risk management is an integral part of the proposed framework. The system embeds risk assessment modules that use the predicted volatility and market sentiment to calculate potential risks and assess the impact of sudden economic or geopolitical events. These modules ensure that the investment recommendations are robust, even during periods of market turbulence. For example, sudden shifts in market sentiment, as might be triggered by unexpected political events or economic crises, are factored into the risk models to help mitigate potential losses. The practical application of this framework is validated using real-world datasets. The system uses historical stock prices, macroeconomic indicators, and financial text corpora to train and validate the models. A robust backtesting mechanism is implemented to evaluate the performance of the predictive models and portfolio strategies. The backtesting process compares the model’s recommendations against benchmark indices like the S&P 500 Index, employing key performance metrics such as Sharpe Ratio, Annualized Return, and Maximum Drawdown. These metrics help to measure the risk-adjusted returns and overall effectiveness of the strategies, providing insights into their potential for real-world application. One of the key challenges addressed by the framework is data quality. Financial markets are often characterized by noisy, sparse, and incomplete data, which can significantly affect the performance of predictive models. The research discusses techniques for handling such challenges, ensuring that the system can process real-time market data while maintaining high levels of accuracy. Additionally, the system is designed to comply with regulatory standards, ensuring that its recommendations align with legal and ethical guidelines for financial decision-making. Overall, this research demonstrates the potential of Large Language Models in revolutionizing financial analysis. By combining the power of natural language processing with advanced financial modeling, the proposed framework offers a more holistic and accurate view of market conditions. The results show significant improvements in prediction accuracy, risk-adjusted returns, and interpretability, paving the way for innovative, scalable, and user-friendly applications that can be employed by both institutional and retail investors. As financial markets continue to evolve, the integration of LLMs offers a promising future for automated financial decision-making, helping investors navigate the complexities of the modern market with confidence.